E-Module Using Van Hiele Phases of Learning to Improve Student’s Mathematical Creative Thinking Skills - Aliq Fiya Kamalasari; Y.L. Sukestiyarno; Adi Nur Cahyono (Unnes Journal of Mathematics Education Research, 2022)
The aim of this study is to (1) develop a web-based e-module based on the Van Hiele Learning Phases and (2) assess the validity, practicability, and effectiveness of an e-module based on the Van Hiele Phases of Learning to enhance creative thinking skills. The research method was R&D by using ADDIE (analysis, design, development, implementation, evaluation) model. The students in this study have been from SMP Negeri 21 Semarang's VII grade. The Discovery Learning approach is used to implement e-modules in learning. And, according to the evaluation of the implementation of this e-module, the value of improving students' creative thinking capacity reveals that the average percentage improvement in the experimental class is 47% greater than the control class, which is 39%. The results of the classical completion test revealed that the average creative thinking capacity of students who took the Van Hiele e-module was greater than 75. (KKM) The comparison test results showed that the average gain in students' creative thinking skills in the experimental class was greater compared to the control class with a sig 0.037<0.005, indicating that the implementation of the e-module with the Van Hiele phase satisfies the effectiveness requirements. This study suggests that teaching materials be improved with more complete material, questions focused at higher order thinking abilities, and other mathematical skills.